Earning Persistence from Operational Cash Flow, Earnings Management, and Debt Policy - Febriani, Cika; Firmansyah, Amrie (Universitas Pamulang, 2022)
This study examines operating cash flow, earnings management, and debt policy on earnings persistence. This study employs a quantitative method approach. The research data is sourced from the financial statements of companies in the infrastructure, utilities, and transportation sectors listed on the Indonesia Stock Exchange for the period 2016 to 2020. The research data is sourced from www.idx.co.id, www.idnfinancials.com and the company's official website. Based on purposive sampling, the total research sample was 145 observations. Hypothesis testing is conducted by using multiple linear regression analysis for panel data. The results suggest that operating cash flow and debt policy are negatively associated with earnings persistence, while earnings management is not associated with earnings persistence. This research indicates that the Indonesia Financial Services Authority is to improve policies related to the financial reporting integrity of Indonesia-listed companies. In addition, the Authority needs to increase supervision over manager policies that can harm the interests of shareholders to improve corporate governance.